2014
DOI: 10.1021/nn406302j
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Magnetic Fields Remote-Control ApoptosisviaNanoparticle Rotation

Abstract: The ability to control the movement of nanoparticles remotely and with high precision would have far-reaching implications in many areas of nanotechnology. We have designed a unique dynamic magnetic field (DMF) generator that can induce rotational movements of superparamagnetic iron oxide nanoparticles (SPIONs). We examined whether the rotational nanoparticle movement could be used for remote induction of cell death by injuring lysosomal membrane structures. We further hypothesized that the shear forces create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
201
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(218 citation statements)
references
References 45 publications
8
201
1
8
Order By: Relevance
“…Nanocarriers combine chemotherapy with physically destructive modalities that induce tumor ablation (photothermal/magnetic) [218][219][220][221][222][223][224][225][226][227][228][229][230][231][232][233][234][235][236]245,246], generate reactive oxygen species (photodynamic) [232][233][234][235][236][237][238][239][240][241][242], and form of free radicals (radiotherapy) to maximize cancer eradication [243]. [246] and demonstrated higher anticancer activity in vitro and in vivo than PTX/PLGA/HAuNPs microspheres alone (no NIR-irradiation) or PLGA/HAuNPs microspheres (no PTX) with NIR irradiation. DOXloaded, PEG-conjugated hollow gold nanoparticles (DOX/PEG/ HAuNPs) demonstrated NIR-triggered, pH-dependent DOX release led to greater antitumor activity and decreased systemic toxicity than free DOX or liposomal DOX [218,219].…”
Section: Combined Photothermal and Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Nanocarriers combine chemotherapy with physically destructive modalities that induce tumor ablation (photothermal/magnetic) [218][219][220][221][222][223][224][225][226][227][228][229][230][231][232][233][234][235][236]245,246], generate reactive oxygen species (photodynamic) [232][233][234][235][236][237][238][239][240][241][242], and form of free radicals (radiotherapy) to maximize cancer eradication [243]. [246] and demonstrated higher anticancer activity in vitro and in vivo than PTX/PLGA/HAuNPs microspheres alone (no NIR-irradiation) or PLGA/HAuNPs microspheres (no PTX) with NIR irradiation. DOXloaded, PEG-conjugated hollow gold nanoparticles (DOX/PEG/ HAuNPs) demonstrated NIR-triggered, pH-dependent DOX release led to greater antitumor activity and decreased systemic toxicity than free DOX or liposomal DOX [218,219].…”
Section: Combined Photothermal and Chemotherapymentioning
confidence: 99%
“…The pairing led to complete tumor eradication in vivo but the individual treatments only inhibited tumor growth, indicating the strong synergistic effect. In another approach, superparamagnetic iron oxide NPs (SPIONs) conjugated with lysosomal protein LAMP1-targeting antibodies induced apoptosis upon rotation activation by exposure to a magnetic field [246]. The NPs accumulated along the membrane in lysosomes due to the conjugated antibodies in rat insulinoma tumor cells and human pancreatic beta cells.…”
Section: Further Modes Of Physical Ablationmentioning
confidence: 99%
“…Zhang et al demonstrated that isotropous Fe 3 O 4 nanoparticles could be rotationally activated in a unique dynamic magnetic field (20 Hz) and after MNPs were internalized into cells and bound to lysosomes, the rotationally activated MNPs generated shear forces which resulted in rapid decrease in size and number of lysosomes, attributable to tearing of the lysosomal membrane [41]. With regard to the effect induced by rotating MNPs under the magnetic field, Yue et al theoretically investigated the interaction mechanism between lipid membranes and rotating MNPs through simulation and found that the rotating nanoparticles promoted cell uptake and also induced the mechanical membrane rupture [89].…”
Section: Under Constant or Low Frequency Magnetic Fieldmentioning
confidence: 99%
“…On the other hand, magnetic nanoparticles, especially of iron oxides, are being used in biomedicine for treatment as hyperthermia or drug delivery [6][7][8][9]. Recently, the possibility of using nickel nanowires in biomedicine has been also proposed [10][11][12].…”
Section: Introductionmentioning
confidence: 99%